Females with Fabry disease: an expert opinion on diagnosis, clinical management, current challenges and unmet needs - Tuttolomondo, Antonino; Chimenti, Cristina; Cianci, Vittoria; Gallieni, Maurizio; Lanzillo, Chiara; La Russa, Antonella; Limongelli, Giuseppe; Mignani, Renzo; Olivotto, Iacopo; Pieruzzi, Federico; Pisani, Antonio (Frontiers in Cardiovascular Medicine, 2025)
Females with Fabry disease (FD) often have a milder phenotype, later symptom onset, and slower disease progression than males, causing delayed diagnosis and undertreatment. A survey was conducted at nine Italian FD centers to evaluate routine management of females with FD; results were discussed at a meeting of eleven Italian specialists and recommendations developed. Of the 227 females managed by the physicians surveyed, 85% were diagnosed through family screening and 38.5% were symptomatic at presentation. Female patients usually underwent cardiac, renal, and neurologic monitoring, and measurement of plasma lyso-globotriaosylsphingosine (Gb3) levels at 6- or 12-month intervals. Treatment was initiated in 54%, mostly enzyme replacement therapy. Experts recommended screening all female relatives of index cases and evaluating all potentially affected organ systems. Diagnosis should be based on genetic analysis. Individualized monitoring of asymptomatic females must balance the need to detect organ damage while maintaining adherence. Treatment decisions should be based primarily on signs/symptoms of FD, but age, family screening results, GLA mutations, Gb3/lyso-Gb3 accumulation, and organ damage should be considered in asymptomatic females. More research on FD in females is needed and physicians should be aware of differences in the diagnosis, monitoring, and management of females vs. males with FD.